1970
DOI: 10.1093/jaoac/53.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Availability Of Iron

Abstract: The high incidence of iron deficiency anemia in the United States and elsewhere is caused by insufficient iron intake, plus poor utilization of many dietary sources of iron. There is need to select assimilable sources of iron for fortification of foods; animal studies show that many of the iron compounds used for cereal enrichment are poorly utilized. A method to measure availability of iron is proposed and is currently being studied collaboratively. Preliminary data indicate that in vitro solubility tests are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1972
1972
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…As has been emphasized, the primary merit of a well designed bioassay procedure involving dose-response curves of both the standard and the unknowns is that the data obtained allow one to determine whether the assay is valid and also the precision of the estimated potency. Such data cannot be obtained if only a single dose of the unknown is tested, as has been recommended (Pla and Fritz, 1970). The five iron salts we have tested were the same samples utilized in the collaborative assays (Pla and Fritz, 1971).…”
Section: Potencymentioning
confidence: 99%
See 1 more Smart Citation
“…As has been emphasized, the primary merit of a well designed bioassay procedure involving dose-response curves of both the standard and the unknowns is that the data obtained allow one to determine whether the assay is valid and also the precision of the estimated potency. Such data cannot be obtained if only a single dose of the unknown is tested, as has been recommended (Pla and Fritz, 1970). The five iron salts we have tested were the same samples utilized in the collaborative assays (Pla and Fritz, 1971).…”
Section: Potencymentioning
confidence: 99%
“…Considerable effort was made in this direction many years ago at about the time when iron fortification was begun (Elvehjem and Kemmerer, 1933;Smith and Otis, 1937;Andrews et al, 1939; Freeman and Burrill, 1945), but little attention has been given to the problem in recent years. Fritz and his collaborators (1970) have revived efforts in this field and have proposed an assay method using either rats or chicks (Pla and Fritz, 1970). This paper reports the results obtained in applying a standard "sloperatio" assay in either rats or chicks.…”
mentioning
confidence: 99%
“…products containing ferrous fumarate, One-A-Day plus Iron and One-A-Day plus Minerals, were not completely soluble in 1.5 N HC1. These results were not surprising since Pla and Fritz (1970) reported that ferrous fumarate was only 57.7% soluble in 50 times its weight of HC1 at pH 1.1 after 72 h.…”
Section: Discussionmentioning
confidence: 61%
“…It is generally assumed that foods must be broken down and rendered soluble in digestive juices if they are to be absorbed. However, attempts to correlate solubility of a substance in acid with the bioavailability of the iron it contains have not been very successful (Pla and Fritz, 1970;Jacobs and Greenman, 1969), except in the case of reduced iron (Pla et al, 1976). We examined the water solubility of the iron in these supplements to be sure that all test animals would receive the same dose of iron.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies performed by Fritz et al (8,20,21) of the biological availability of iron in iron-depleted chicks and rats also indicated that ferrous sulphate has a high relative biological value compared with other iron compounds. It was also found that ferrous sulphate added to a biscuit mix prior to baking was utilized nearly as well as the same quantity of ferrous sulphate added directly to the test diet (8).…”
mentioning
confidence: 99%